Green Supply Chain Management and Corporate Performance Among Manufacturing Firms in Pakistan - Qalati, Sikandar Ali; Kumari, Sonia; Soomro, Ishfaque Ahmed; Ali, Rajib; Hong, Yifan (Frontiers in Environmental Science, 2022)
A common perception is lowering the environmental consequences of firms’ supply chain activities is a costly idea that poses a challenge to the corporate world. The study aims to examine the relationship between green supply chain management (GSCM) and corporate performance among listed firms in Pakistan, using the general panel method of moments (GMM) and ANOVA techniques. At the same time, the Granger causality technique provides robust results. The study focused on manufacturing firms, covering periods of 2009-2020. The study engaged a modified balanced scorecard framework to adopt five metrics of corporate performance, namely: gross profit ratio, net profit ratio, customer dimension, learning growth dimension, and efficiency dimension. The study incorporated the two measures of the GSCM initiative and two control variables. Findings from the panel GMM estimates reveal that GSCM positively and negatively impacted the five corporate performance metrics explored. ANOVA results indicate significant differences in customer satisfaction, profitability, and efficiency performance metrics among the top and low GSCM practicing corporations. On the other hand, Granger causality results specify a moderate causal association between GSCM implementation and firm performance in Pakistan. Implying that poor GSCM practice may not yield the expected benefits; instead, conscientious efforts should be put in place to ensure that practicing GSCM initiative should be effectively done.